Efficacy and safety of iron-chelation therapy with deferoxamine, deferiprone, and deferasirox for the treatment of iron-loaded patients with non-transfusion-dependent thalassemia syndromes - Kontoghiorghe, Christina N (Drug Des Devel Ther, 2016)
The prevalence rate of thalassemia, which is endemic in Southeast Asia, the Middle East, and the Mediterranean, exceeds 100,000 live births per year. There are many genetic variants in thalassemia with different pathological severity, ranging from a mild and asymptomatic anemia to life-threatening clinical effects, requiring lifelong treatment, such as regular transfusions in thalassemia major (TM). Some of the thalassemias are non-transfusion-dependent, including many thalassemia intermedia (TI) variants, where iron overload is caused by chronic increase in iron absorption due to ineffective erythropoiesis. Many TI patients receive occasional transfusions. The rate of iron overloading in TI is much slower in comparison to TM patients. Iron toxicity in TI is usually manifested by the age of 30–40 years, and in TM by the age of 10 years. Subcutaneous deferoxamine (DFO), oral deferiprone (L(1)), and DFO–L(1) combinations have been effectively used for more than 20 years for the treatment of iron overload in TM and TI patients, causing a significant reduction in morbidity and mortality. Selected protocols using DFO, L(1), and their combination can be designed for personalized chelation therapy in TI, which can effectively and safely remove all the excess toxic iron and prevent cardiac, liver, and other organ damage. Both L(1) and DF could also prevent iron absorption. The new oral chelator deferasirox (DFX) increases iron excretion and decreases liver iron in TM and TI. There are drawbacks in the use of DFX in TI, such as limitations related to dose, toxicity, and cost, iron load of the patients, and ineffective removal of excess iron from the heart. Furthermore, DFX appears to increase iron and other toxic metal absorption. Future treatments of TI and related iron-loading conditions could involve the use of the iron-chelating drugs and other drug combinations not only for increasing iron excretion but also for preventing iron absorption.